محددات صحافة الحلول في المواقع الإخبارية الإلكترونية وانعكاساتها على القائم بالاتصال والجمهور - أنور، رحاب محمد (جامعة القاهرة - كلية الإعلام - قسم الصحافة, 2022)
جاءت هذه الدراسة لرصد أبرز محددات صحافة الحلول في المواقع الإخبارية الإلكترونية المصرية، وكذلك رصد تصورات المحررين الصحفيين حول هذه الصحافة وأهميتها في بيئة العمل الصحفي، وتأثير ممارستهم لهذا النوع على الرضا الوظيفي لديهم، وكذلك التعرف على الآثار الإيجابية لتعرض الشباب الجامعي الصحافة الحلول. منهج الدراسة: اعتمدت الدراسة على منهج المسح بشقيه الوصفي والتحليلي. وطبقت الدراسة ثلاثة أدوات بحثية هي: تحليل المضمون لتحليل المحتوى الإعلامي للموقع عينة الدراسة الخاص بصحافة الحلول خلال عام 2018، والمقابلة المتعمقة للحصول على بيانات تفصيلية لتصورات المحررين الصحفيين حول صحافة الحلول وأهميتها في بيئة العمل الصحفي، وتأثيرها عليهم والمستقبل الذي يتوقعونه لها من وجهة نظرهم، ومجموعات النقاش المركزة مع عينة من الشباب الجامعي عرضتهم الباحثة لموضوعات صحافة الحلول. الإطار النظري للدراسة: اعتمدت الدراسة في إطارها النظري على مدخل تكاملي في محاولة لتلبية أغراض الدراسة وقد اشتمل على نظرية المسئولية الاجتماعية، ونموذج هرم التأثيرات الشوميكر Shoemaker وريس Reese، ونظرية إدارة المزاج Mood Management Theory نتائج الدراسة: نتائج الدراسة التحليلية: توصلت نتائج الدراسة التحليلية التي طبقت على قصص صحافة الحلول في موقع "مصراوي" خلال عام 2018 إلى أن الموقع التزم إلى حد كبير جدًا بالسمات الرئيسية لصحافة الحلول كما هي في الصحف الغربية، حيث كانت أبرز سمات القصص المعتمدة على الحلول أنها جميعًا تناولت أسباب المشكلة التي عرضت لها الحل، وكلها بلا استثناء تناولت بالشرح الاستجابة للمشكلة أو الحل، والغالبية العظمى منها شرحت تفاصيل حل المشكلة، غالبية القصص المعتمدة على الحلول احتوت على رؤية أو درس قابل للتعلم، وكل القصص دون استثناء ركزت في المقام الأول على كيفية تنفيذ الحل وليس الثناء على الحل أو تعظيمه. نتائج المقابلات المتعمقة: أجمع المحررون الصحفيون -عينة الدراسة -أن السبب الرئيسي وراء اهتمامهم بصحافة الحلول إنما يرجع إلى رغبتهم الشخصية في تقديم أخبار إيجابية ونماذج ملهمة وسط أحداث سيئة موجودة على الساحة، وأكدوا على أن مشاركتهم في إجراء هذا النوع من الصحافة كان له تأثيره الإيجابي عليهم وعلى شعورهم بالسعادة والتفاؤل، وهو ما يعكس أهمية ممارسة هذا النوع من الصحافة على القائمين بالاتصال لتأثيره الإيجابي الكبير عليهم. نتائج جماعة النقاش المركزة: أجمع المشاركون في مجموعة النقاش على شعورهم بالتفاؤل بعد قراءتهم لهذه القصص المعتمدة على الحلول، وعلى زيادة معرفتهم حول القضية بعد قراءتهم لهذا النوع من القصص. وأجمع المبحوثون على أن قراءتهم لقصص صحافة الحلول زادت من رغبتهم في قراءة قصص مشابهة تتناول الحلول. This study was conducted to monitor the most prominent determinants of the solutions journalism in Egyptian online news sites, as well as to monitor the perceptions of journalists about this press and its importance in the journalistic work environment, the impact of their practice on job satisfaction, as well as to identify the positive effects of the exposure of university youth to the solutions journalism. Method: The study was based on the survey method in both descriptive and analytical aspects. The study applied three research tools: content analysis to analyze the media content of the site sample study for solutions journalism during 2018, an in-depth interview to obtain detailed data on the mass communicator's perceptions of the solutions journalism, its impact on them and the future they expect from their point of view, and focused discussion groups with a sample of university youth presented by the researcher for the topics of the solutions journalism. Theoretical framework of the study: In its theoretical framework, the study relied on an integrative input in an effort to meet the purposes of the study, and included the theory of social responsibility, the model of the pyramid of influences of Shoemaker and Reese Reese, and mood management theory. Study results: Results of the analytical study: The results of the analytical study applied to the stories of the solutions journalism in the site "Masrawy" during 2018 found that the site adhered to very much the main features of the solutions journalism as it is in the Western newspapers, where the most prominent features of the stories based on solutions that all dealt with the causes of the problem offered to her solution, all without exception addressed by explaining the response to the problem or the solution, and the vast majority of them explained the details of solving the problem, the majority of stories based on solutions contained a vision or a lesson learned, and all Stories without exception focused primarily on how to implement the solution and not praise the solution or maximize it. In-depth interview results: The editors of the press - sample study - that the main reason for their interest in the solutions journalism is because of their personal desire to provide positive news and inspiring models amid bad events on the scene, and stressed that their participation in conducting this type of journalism had a positive impact on them and their sense of happiness and optimism, which reflects the importance of practicing this type of journalism on those who communicate because of its great positive impact on them. The results of the focused discussion group: The panellists were unanimous in their sense of optimism after reading these solutions-based stories, and on increasing their knowledge of the issue after reading this type of story. The sample agreed that their reading of the stories of the solutions journalism increased their desire to read similar stories about solutions.
Keywords: الصحافة المصرية -- صحافة الحلول -- المواقع الإلكترونية -- المحررون الصحفيون -- الرضا الوظيفي